Quality Control of Puff Pastry Sheet Production Process at CV. PRS Bali - Ayu Suardani; A.A. Made Semariyani; I Putu Candra; I Wayan Sudiarta; I Nyoman Rudianta; Ni Kadek Karina Saridewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Puff pastry is a pastry product made from a mixture of flour, sugar, salt and fat/butter. To produce good quality Puff Pastry, good quality raw materials are needed. Quality control are techniques or operational activities used to meet quality requirements. Quality control of the production process can be considered to be correct if the quality is in accordance with the quality criteria, the performance of equipment, processes and products and if the deviations are identifiable or reportable. Puff pastry sheet production process carried out at CV. PRS includes: the process of preparing materials, weighing materials, mixing materials, cutting and weighing dough according to standard weights, plastic packaging, cooling dough, flattening dough, molding and cutting according to standard sizes, cooling and packaging of products.